Ants of Brazil: an overview based on 50 years of diversity studies. Issue 1 (31st December 2022) - Feitosa, Rodrigo M.; Camacho, Gabriela P.; Silva, Thiago S. R.; Ulysséa, Mônica A.; Ladino, Natalia; Oliveira, Aline M.; Albuquerque, Emília Z.; Schmidt, Fernando A.; Ribas, Carla R.; Nogueira, Anselmo; Baccaro, Fabrício B.; Queiroz, Antônio C. M.; et al.
Abstract : Despite the historical efforts to list and organize the taxonomic knowledge about the Brazilian ant fauna, the most diverse in the world, several gaps regarding species distribution data and sampling coverage persist. In an attempt to fill some of these gaps, we here apply a scientometric approach to provide an updated overview of the ants of Brazil based on formal publications on ant diversity in the Brazilian territory. In the last 50 years, ant diversity studies in Brazil revealed 1130 species, corresponding to around 70% of the species known to occur in the country. The Brazilian biomes with the highest number of described species recorded were, respectively, the Amazon Forest (716 species), Atlantic Forest (657 species), Cerrado (389 species), Caatinga (185 species), Pantanal (143 species), and Pampa (86 species). Considering the number and frequency of unidentified species, the genera Azteca, Hypoponera, Pheidole, and Solenopsis represent the main knowledge frontiers regarding taxonomic resolution, with more than 80% of their records associated with morphospecies codes in diversity studies in Brazil. Moreover, around 7.5% of the papers presented inconsistences in their species lists regarding the validity of taxonomic names, and we found studies for which some taxa records are geographically implausible. Besides demonstrating the importance of ecological publications to the ant diversity knowledge in Brazil, our findings highlight a strong sampling bias in ant occurrence data in the country, with species records unevenly distributed across Brazilian biomes. In short, our results constitute valuable information for future projects on ant taxonomy and surveying in Brazilian natural areas.